2015
DOI: 10.1089/jmf.2014.0103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pomegranate Extract Supplementation on Cardiovascular Risk Factors and Physical Function in Hemodialysis Patients

Abstract: The purpose of this study was to evaluate the effects of oral supplementation with pomegranate extract on cardiovascular risk, physical function, oxidative stress, and inflammation in hemodialysis (HD) patients. Thirty-three HD subjects were randomized to the pomegranate (POM) or placebo (CON) group. Patients in POM ingested a 1000 mg capsule of a purified pomegranate polyphenol extract 7 days/week for 6 months. Individuals in CON ingested a noncaloric placebo capsule using the same protocol. Measurements were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(92 citation statements)
references
References 57 publications
4
85
1
Order By: Relevance
“…In contrast to blood pressure, evidence regarding the effect of pomegranate on blood lipids of hemodialysis patients is rather controversial. Studies confirmed our results for serum triglyceride and HDL cholesterol improvement by pomegranate, but two other investigations reported no effect of either pomegranate polyphenol or PJ on these lipid profiles. Some of the controversy over the results of different studies may be explained by the baseline values of triglycerides and HDL cholesterol which probably should be at unfavorable levels in order for pomegranate to exert its benefit.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast to blood pressure, evidence regarding the effect of pomegranate on blood lipids of hemodialysis patients is rather controversial. Studies confirmed our results for serum triglyceride and HDL cholesterol improvement by pomegranate, but two other investigations reported no effect of either pomegranate polyphenol or PJ on these lipid profiles. Some of the controversy over the results of different studies may be explained by the baseline values of triglycerides and HDL cholesterol which probably should be at unfavorable levels in order for pomegranate to exert its benefit.…”
Section: Discussionsupporting
confidence: 91%
“…Once again, pomegranate may not exert these effects in non‐oxidative stress conditions or if administered in pre‐dialysis states . Also, such beneficial effects have not been observed in high doses of pomegranate and long interventions . The beneficial effects of pomegranate are attributed to polyphenols .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher dose (10 mL/day) pomegranate extract for 12 weeks was found to increase PON1 in patients with active rheumatoid arthritis [48]. In hemodialyzed patients, daily administration of 1000 mg of a purified pomegranate polyphenol extract for six months increased PON1 activity [52]. Pomegranate juice, or its purified phenolic compounds punicalagin, gallic acid, or ellagic acid, promote binding of a labeled recombinant PON1 to HDL in vitro [49].…”
Section: Pomegranate Juicementioning
confidence: 99%
“…Juice, seeds, leaves, flowers, bark and roots of pomegranate have various effects. Lowering fever, treating diabetes, anthelmintic, anti-diarrhea, blood tonic, stopping the bleeding, and healing ulcers are the most important traditional uses of pomegranate [10][11][12][13][14] .…”
mentioning
confidence: 99%